KARAKTERISASI DAN AKTIVITAS ANTIOKSIDAN SEDIAAN MINYAK HERBAL DARI VCO DENGAN BERBAGAI PERBANDINGAN BERAT REMPAH - Andreas, Andreas; Wibowo, Muhamad Agus; Jayuska, Afghani (Indonesian Journal of Pure and Applied Chemistry, 2026)
This study aimed to characterize the phytochemical compounds and to evaluate the antioxidant activity and SPF value of an herbal oil preparation based on VCO, formulated with five spices: elephant ginger, galangal, lemongrass, Java turmeric, and bidara leaves. The herbal oil was prepared by heating for 60 minutes with varying spice weights (30–80 grams) in 300 mL of VCO. Phytochemical screening was conducted qualitatively to detect the presence of alkaloids, flavonoids, phenols, saponins, and steroids/terpenoids. Antioxidant activity was analyzed using the DPPH method, and the IC₅₀ value was determined through linear regression. The SPF value was calculated spectrophotometrically using the Mansur equation. Results showed that all formulations contained active phytochemical compounds. The formulation with 60 grams of spices exhibited the highest antioxidant activity (IC₅₀ = 507.577 ppm, classified as weak) and an SPF value of 45.426 (ultra protection category). The addition of spices significantly enhanced the bioactive content and the effectiveness of VCO as a natural antioxidant and sunscreen agent.